(untitled) (Web of Teachers: Inderscience Research, 2025)
Teaching pronunciation to elementary school students is an essential part of language learning that provide the foundation for effective communication and negotiation skills, This article provides practical ways to make pronunciation more attractive like native speakers and age-appropriate for young learners. Key strategies include incorporating playful and interesting activities, for example, songs, videos, and games, to make learning process enjoyable and interactive. It puts much emphasize on the significance of modeling correct pronunciation and creating a supportive atmosphere that encourages practice without fear of making mistakes in front of others. The use of these approaches, such as visual aids and kinesthetic activities, is debated to contribute to the diverse learning styles. Additionally, the article indicate the role of repetition, consistent feedback, and integrating pronunciation into everyday classroom lessons. By adopting these techniques, teachers can help elementary school students develop clear and understandable pronunciation skills while fostering a lifelong interesting language learning.